Defective human immunodeficiency virus-specific CD8+ T-cell polyfunctionality, proliferation, and cytotoxicity are not restored by antiretroviral therapy - Migueles, Stephen A; Weeks, Kristin A; Nou, Eric; Berkley, Amy M; Rood, Julia E; Osborne, Christine M; Hallahan, Claire W; Cogliano-Shutta, Nancy A; Metcalf, Julia A; McLaughlin, Mary; Kwan, Richard; Mican, JoAnn M; et al. (Journal of virology, 2009)
Identifying the functions of human immunodeficiency virus (HIV)-specific CD8+ T cells that are not merely modulated by the level of virus but clearly distinguish patients with immune control from those without such control is of paramount importance. Features of the HIV-specific CD8+ T-cell response in antiretroviral-treated patients (designated Rx <50) and untreated patients (long-term nonprogressors [LTNP]) matched for very low HIV RNA levels were comprehensively examined. The proliferative capacity of HIV-specific CD8+ T cells was not restored in Rx <50 to the level observed in LTNP, even though HIV-specific CD4+ T-cell proliferation in the two patient groups was comparable. This diminished HIV-specific CD8+ T-cell proliferation in Rx <50 was primarily due to a smaller fraction of antigen-specific cells recruited to divide and not to the numbers of divisions that proliferating cells had undergone. Exogenous interleukin-2 (IL-2) induced proliferating cells to divide further but did not rescue the majority of antigen-specific cells with defective proliferation. In addition, differences in HIV-specific CD8+ T-cell proliferation could not be attributed to differences in cellular subsets bearing a memory phenotype, IL-2 production, or PD-1 expression. Although polyfunctionality of HIV-specific CD8+ T cells in Rx <50 was not restored to the levels observed in LTNP despite prolonged suppression of HIV RNA levels, per-cell cytotoxic capacity was the functional feature that most clearly distinguished the cells of LTNP from those of Rx <50. Taken together, these data suggest that there are selective qualitative abnormalities within the HIV-specific CD8+ T-cell compartment that persist under conditions of low levels of antigen.